2024
DOI: 10.1186/s13148-023-01618-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the therapeutic potential of Sirt6-enriched adipose stem cell-derived exosomes in myocardial ischemia–reperfusion injury: unfolding new epigenetic frontiers

Kun Liu,
Hecheng Wang,
Yiou Wang
et al.

Abstract: Background The management of myocardial ischemia–reperfusion injury (MIRI) presents continuous therapeutic challenges. NAD-dependent deacetylase Sirtuin 6 (Sirt6) plays distinct roles in various disease contexts and is hence investigated for potential therapeutic applications for MIRI. This study aimed to examine the impact of Sirt6-overexpressing exosomes derived from adipose stem cells (S-ASC-Exo) on MIRI, focusing on their influence on AIM2-pyroptosis and mitophagy processes. The sirtuin fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…SIRT6 emerges as a quintessential member of the Sirtuin family, endowed with capabilities to attenuate oxidative stress, counter cellular autophagy, avert apoptosis, and forestall cellular aging and tumorigenesis (Liu et al, 2021). Increasing studies have revealed the connection between SIRT6 and cardiac protection, highlighting its pivotal role in cardiomyocyte preservation (Liu et al, 2024). The de ciency of SIRT6 in mice results in myocardial mitochondrial damage akin to that observed in aged mice (Divya et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT6 emerges as a quintessential member of the Sirtuin family, endowed with capabilities to attenuate oxidative stress, counter cellular autophagy, avert apoptosis, and forestall cellular aging and tumorigenesis (Liu et al, 2021). Increasing studies have revealed the connection between SIRT6 and cardiac protection, highlighting its pivotal role in cardiomyocyte preservation (Liu et al, 2024). The de ciency of SIRT6 in mice results in myocardial mitochondrial damage akin to that observed in aged mice (Divya et al, 2024).…”
Section: Discussionmentioning
confidence: 99%